TFIIB aptamers inhibit transcription by perturbing PIC formation at distinct stages - Sevilimedu, Aarti (Oxford University Press, 2008)
Transcription in eukaryotes is a multistep process involving the assembly and disassembly of numerous inter- and intramolecular interactions between transcription factors and nucleic acids. The roles of each of these interactions and the regions responsible for them have been identified and studied primarily by the use of mutants, which destroy the inherent properties of the interacting surface. A less intrusive but potentially effective way to study the interactions as well as the surfaces responsible for them is the use of RNA aptamers that bind to the interacting factors. Here, we report the isolation and characterization of high-affinity RNA aptamers that bind to the yeast general transcription factor TFIIB. These aptamers fall into two classes that interfere with TFIIB's interactions with either TBP or RNA polymerase II, both of which are crucial for transcription in yeast. We demonstrate the high affinity and specificity of these reagents, their effect on transcription and preinitiation complex formation and discuss their potential use to address mechanistic questions in vitro as well as in vivo.